2016
DOI: 10.14202/vetworld.2016.1025-1027
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Peste des petits ruminants virus and goatpox virus from an outbreak in goats with high mortality in Meghalaya state, India

Abstract: Aim:We describe a laboratory investigation carried out to confirm the etiology of the heavy mortality (37 animals died out of total 44, i.e. 84%) in goats in Ri-Bhoi district of Meghalaya, Northeast region of India in December 2015. The clinical signs observed were abortion, diarrhea, high fever (up to 104°F), pox lesion in the skin, and respiratory distress.Materials and Methods:The samples comprising whole blood, sera, and pox lesion were collected from the animals (n=7) from an outbreak for the screening of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…In this study, we did not assay for these pathogens, but sheep and goat pox and CCPP were diagnosed based on typical clinical signs in flocks that neighboured confirmed PPRV-infected flocks. Co-infection of PPRV with capripoxvirus has been reported in the Democratic Republic of Congo [60] and in India [61,62]. Peri-oral skin lesions were present in some flocks but not others, which raises the question of whether the lesions were due to PPRV infection or due to co-infection with other pathogens such as orf virus or bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we did not assay for these pathogens, but sheep and goat pox and CCPP were diagnosed based on typical clinical signs in flocks that neighboured confirmed PPRV-infected flocks. Co-infection of PPRV with capripoxvirus has been reported in the Democratic Republic of Congo [60] and in India [61,62]. Peri-oral skin lesions were present in some flocks but not others, which raises the question of whether the lesions were due to PPRV infection or due to co-infection with other pathogens such as orf virus or bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…() and Karim et al . () respectively in co‐infections of PPR and GTP in India among flocks of goats. Mixed infections are a common occurrence in livestock production with severe economic consequences compared to singular infections (Malik et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similar finding were observed by Kulkarni et al, (1996) who reported significantly higher case fatality rate in kids. This might be due to for higher infection of young ones with subclinical coccidiosis causing immunosuppressive effect or Escherichia coli infection causing fimbrial adhesions with intestinal mucosa and thus enhancing the effect of PPR virus (Kumar et al, 2001).The morbidity rate can reach 100% with a high case fatality rate in the acute form of disease (Pope et al, 2013;Karim et al, 2016). Affected goats showed high fever (105-107 o F) ocular and nasal discharges ( Fig.1) and diarrhea with soiling of hindquarters.…”
Section: Resultsmentioning
confidence: 99%